Profitability of commercial and industrial photovoltaics and battery projects in South-East-Asia. (1st August 2020) - Beuse, Martin; Dirksmeier, Mathias; Steffen, Bjarne; Schmidt, Tobias S.
Highlights: Assesses photovoltaics and battery project at commercial and industrial customers. Studies applications in three industries and three South-East Asian countries. Finds that profitable photovoltaic and battery investments exist already today. Shows that adding a battery often reduces profitability vis-à-vis photovoltaic only. Derives policy advice to foster the deployment of photovoltaic and battery projects. Abstract: Solar photovoltaics and batteries are key technologies to enable a rapid decarbonization of electricity systems. Commercial & industrial consumers are an important market for these technologies due to their fast growing electricity demand, particularly in emerging economies. However, it remains unclear if photovoltaics and battery installations are profitable for commercial & industrial applications in an emerging country context. Assessing the profitability of investments in photovoltaics and battery projects, however, is much more complex than for standalone photovoltaics projects, and strongly depends on the regulatory regime. These regimes are often complex and can be inconsistent. Hitherto decision makers lack models which are suitable for detailed assessments and which can serve as basis to adjust the regime. Here, we develop a techno-economic optimization model for commercial & industrial photovoltaics and battery projects, which returns a profit-maximizing storage dispatch and system design. We investigate three South-East Asian countries (Vietnam, Thailand, and Malaysia) and three different industries (Textile, Consumer Goods, and Electronics). The results show that profitable investment opportunities in photovoltaics and battery projects exist already today, even though a battery typically reduces profitability vis-à-vis standalone photovoltaics projects. We discuss how reducing investment risks, building local industries, and shifting existing support schemes towards batteries could support battery deployment in South-East Asia and thereby contribute to the decarbonization of electricity systems in the region.